Emergent Public Health Issues in the US-Mexico Border Region - Jill Eileen Guernsey De Zapien (Frontiers Research Topics, 2017)
US-Mexico border region area has unique social, demographic and policy forces at work that shape the health of its residents as well as serves as a microcosm of migration health challenges facing an increasingly mobile and globalized world. This region reflects the largest migratory flow between any two nations in the world. Data from the Pew Research Center shows over the last 25 years there has never been lower than 140,000 annual immigrants from Mexico to the United States (with peaks over 700,000). This migratory route is extremely hazardous due to natural (e.g., arid and hot desert regions) and human made barriers as well as border enforcement practices tied to socio-political and geopolitical pressures. Also, reflecting the national interdependency of public health and human services needs, during the most recent five year period surveyed the migratory flow between the US and Mexico has equaled that of the flow of Mexico to the US--both around 1.4 million persons. Of particular public health concern, within the US-Mexico region of both nations there is among the highest disparities in income, education, infrastructure and access to health care--factors within the World Health Organization's conceptualization of the Social Determinants of Health, and among the highest rates of chronic disease. For instance obesity and diabetes rates in this region are among the highest of those monitored in the world, with adult population estimates of the former over 40% and estimates in some population sub-groups for the latter over 20%. The publications reflected in this Research Topic, all reviewed from experts in the field, addressed many of the public health issues in the US Mexico Border Health Commission's Healthy Border 2020 objectives. Those objectives-- broad public health goals used to guide a diverse range of government, research and community-based stakeholders--include Non Communicable Diseases (including adult and childhood obesity-related ones; cancer), Infectious Diseases (e.g., tuberculosis; HIV; emerging diseases--particularly mosquito borne illnesses), Maternal and Child Health, Mental Health Disorders, and Motor Vehicle Accidents. Other relevant public health issues affecting this region, for example environmental health, binational health services coordination (e.g., immunization), the impact of migration throughout the Americas and globally in this region, health issues related to the physical climate, access to quality health care, discrimination/mistreatment and well-being, acculturative/immigration stress, violence, substance use/abuse, oral health, respiratory disease, and well-being from a social determinants of health framework, are critical areas addressed in these publications or for future research. Each of these Research Topic publications presented applied solutions (e.g., new programs, technology or infrastructure) and/or public health policy recommendations relevant to each public health challenge addressed.